PENGARUH STRUKTUR ASSET, CAPITAL INTENSITY DAN KEPUTUSAN INVESTASI TERHADAP NILAI PERUSAHAAN - Airria Cipta Adi; Juli Ismanto (Jurnal Nusa Akuntansi, 2026)
The research aims to examine and analyze the influence of asset structure, capital intensity, and investment decisions on firm value. This study uses a sample of property and real estate companies listed on the Indonesia Stock Exchange in 2019-2024. The sampling method for this study was purposive sampling using E-views version 9 to analyze the data. This type of quantitative associative research with an observation period of 6 (six) years, with a population of 92 companies, resulting in a total of 11 observations. Simultaneous observations show that asset structure, capital intensity, and investment decisions influence firm value. Partially, the asset structure variable influences firm value. Meanwhile, the capital intensity variable has no effect, and investment decisions have a positive effect on firm value.